Lembaran Akomodasi dan Intoleransi: Relasi Antar Iman dalam Literatur Keislaman di Indonesia - Siti Khodijah (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2019)
There is a great deal of Islamic literature on the market. This situation provides space to slip in “hidden messages”. Some people turn into figures that have changed 180 degrees after reading a book. The National Standardization Agency (BSN) only controls formal Islamic literature. On the other hand, non-formal literature circulates more widely in society. This article will explain the development of Islamic literature in Indonesia including: distribution, consumers, branding, ideas, and writing techniques. This study highlights Islamic literature when discussing interfaith relations in content and storyline. Each selected representation of Islamic literature has characteristics based on the trendsof each period influenced by socio-political and economic-market factors. Values of diversity are ideally offered in every sample of Islamic literature in accordance with the reality of diversity in Indonesia. There is a big loss if “new piety” is not accompanied by a foundation of tolerant contextualization; such an impact would promote a kind of exclusivity that is the antithesis of what is being lived and instills pride in Islamic literature.[Jumlah literatur keislaman sangat melimpah di pasaran. Situasi ini memberikan ruang untuk menyelipkan “pesan-pesan terselubung” di dalamnya. Beberapa orang berubah menjadi sosok yang berubah 180 derajat setelah membaca sebuah buku. Badan Standarisasi Nasional (BSN) hanya mengkontrol literatur keislaman formal. Pada sisi lain, Literatur non-formal beredar lebih luas dalam masyarakat. Artikel ini akan menjelaskan perkembangan literatur keislaman di Indonesia, meliputi: sebaran, konsumen, branding, gagasan-ide, dan teknik penulisan. Penelitian ini menyoroti literatur keislaman ketika membahas relasi antar iman dalam isi (content) dan alur cerita. Setiap literatur keislaman memiliki karakteristik berdasarkan trend masing-masing periode dipengaruhi oleh faktor sosial-politik dan ekonomi-pasar. Nilai-nilai keragaman idealnya ditawarkan dalam setiap literatur keislaman, sesuai dengan realitas keragaman di Indonesia. Kerugian besar jika “keshalehan baru” tidak disertai dengan landasan kontektualisasi toleransi yang membumbung tinggi. Hal ini berdampak pada eksklusifisme yang kian dihidupi dan dibanggakan dalam literatur keislaman dari masa ke masa.]